High Spectrum Efficiency of MIMO-SC-FDMA for Optical Wireless Communication Systems - Puntsri, Kidsanapong; Suttisopapan, Puripong (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This work aimed to present high spectrum efficiency of single carrier frequency division multiplexing (SC-FDM) together with multiple-input multiple-output (MIMO) for optical wireless communication (OWC) systems. In order to improve signal to noise ratio (SNR), maximum ratio combining (MRC) with frequency diversity was employed. It was compared with the zero forcing detection in higher order MIMO system. Additionally, at the receiver end, due to small diameter size of the avalanche photodetector (APD), the numbers of receiver up to 100 elements were therefore practically applicable. To analyze the proposed systems over OWC channel, the numerical simulation method was used and multi-path indoor environment was assumed. By applying the proposed diversity method, the results clearly showed that the SNR was signifi cantly improved and the high order M-ary QAM (quadrature amplitude modulation) can also be achieved. Furthermore, for 256-QAM, the error free transmission can be achieved with SNR of only 30 dB with 6 number of antennas. In zero forcing detection, the transmission speed was higher than the MRC system when compared with the same bit per symbol. However, it gave higher BER.